The Relationship Between Intramural Fat Accumulation and Sarcopenia on MR Enterography Exams in Patients with Crohn’s Disease - Algin, Oktay; Güneş, Yasin Celal; Cankurtaran, Rasim Eren; Corabay, Seniha; Yurekli, Oyku Tayfur (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Research on magnetic resonance enterography (MRE) and sarcopenia for assessing Crohn’s disease (CD) is growing. Our study examined the connections between the presence of sarcopenia, intramural fat accumulation (IFA), and clinical, laboratory, and MRE findings.This retrospective study was conducted on 112 patients with suspected or diagnosed CD who underwent 3-tesla MRE. The study examined the correlation between sarcopenia-related parameters and MRE findings. Results of MRE exams and clinical and laboratory results were statistically analyzed. The Kruskal-Wallis, Pearson chi-square, and Fisher-Freeman-Halton tests were used for comparison.It was determined that patients with active inflammation on a chronic basis had more IFA than the others (p<0.001). There were positive relationships between IFA and intramural edema (p<0.001). There were positive correlations between IFA and high b-values and negative correlations with apparent diffusion coefficient values (p<0.05). Positively significant relationships were found between IFA and wall thickness, affected segment length, disease duration, and sedimentation values (p<0.05). Strong correlations were found between sarcopenia and the CD activity index as well as wall thickness (p<0.001/p=0.003). There was no significant relationship between steroid usage and other variables.The presence of IFA is associated with chronic inflammation. There was no clear relationship between steroid use and IFA. Our findings support the idea that sarcopenia is related to the activity of CD. Further comprehensive research is required on these subjects.
Keywords: sarcopenia; DWI; MRI; intramural fat; enterography